Edema Paru Non Kardiak - Mulyadi Mulyadi (Jurnal Kedokteran Syiah Kuala, 2010)
Abstrak.  Edema paru terjadi apabila terjadi peningkatan laju filtrasi  membran alveolo kapiler yang melebihi kapasiatas,   Edema paru non kardiak adalah   akumulasi cairan  yang abnormal atau berlebihan  dalam ruang interstitial dan  alveolar  paru akibat peningkatan  penneabilitas  mikro vaskular.  Penyebab edema paru  non kardiak sangat beragam, cidera paru akut, aspirasi dan inhalasi gas toksik, serta akibat infeksi. Penatalaksanaan utama ditujukan pada penyakit dasar, serta meliputi pengobatan non spesifik, pengobatan faktor pencetus, serta bertujuan untuk menjaga oksigenasi jaringan agar tetap adekuat. (JKS 2010,· l:37-42)Kata kunci : edema paru, non kardiak.Abstract. Pulmonary edema occurs when there is an increase speed of alveolo  capillary  filtration membrane that exceeds the capacity. The non-cardiac pulmonary edema is the accumulation of abnormal or excessive fluid in  the interstitial  and alveolar lung spaces due to the increasing of micro vascular permeability.  The causes of non-cardiac edema pulmonary are very diverse which include  acute lung  injuries, aspiration and inhalation of toxic  gases, and also due to infections. The main treatments are aimed to the basic diseases  which include non- specific treatments, treatment of triggerer factors, and it is aimed  to maintain tissue oxygenation as to make it remain adequate. (JKS  2010; 1:37-42)Keywords : non cardiac, pulmonary   edema.